Battery Charger Control System Employing a Buck Converter with Visual Studio Interface - Sandrya, Iqbal; Asnil (Journal of Industrial Automation and Electrical Engineering, 2024)
This research develops a buck converter-based battery charger using the Constant Current Constant Voltage (CCCV) method to enhance reliability and prevent overcharging. A PI Controller is used to obtain the CC and CV parameters for system control. The charging process starts in Constant Current mode at 1.2 A until the battery voltage reaches 12.6 V, then switches to Constant Voltage mode, gradually decreasing the current to a cutoff at 0.07 A. A Visual Studio interface is employed to monitor the charging process, displaying graphs of current, voltage, and State of Charge. Testing with a 2800 mAh lithium-ion 18650 battery showed a charging duration of 2 hours and 43 minutes, with 73 minutes in Constant Current mode and 90 minutes in Constant Voltage mode. Real-time monitoring with the Visual Studio interface has provided an informative understanding of battery charging characteristics based on the CCCV method